Strategies and criteria for foreign language reading materials selection. - Лабінська, Богдана; Паранюк, Дан; Виспінська, Наталія; Коропатніцька, Тетяна (Університет імені Альфреда Нобеля,, 2022)
Reading is of great importance for the modern educational process, as it opens access to leading sources of information, expands people’s outlook, etc. Naturally, reading as a communicative skill and a means of communication is always used at the FL classes. However, the foreign language competence of most Ukrainian teachers remains insufficient. The purpose of the article is to single out the strategies and criteria for selecting the educational material to improve the level of teachers’ foreign language competence in reading. Thus, the current study presents the criteria for selecting the foreign language texts for reading in a due regard to educational, psycholinguistic, linguistic, technical, socio-cultural aspects, with an appropriate set of options for each of them. The strategies of selecting foreign language texts, offered in this research, are relevant to the current tendencies prevailing in the formation of foreign language competence in reading. They include focusing on the topic envisaged by the curriculum and the objectives of the FL class; fixing linguistic, speech, sociocultural aspects that are necessary for the class; applying different ways of highlighting / marking the lexical units and grammar structures; enlarging fonts; providing audio support for students with special educational needs (visually impaired students). The developed strategies and criteria suggest that students with special educational needs should also be able to use the texts. With the aim of determining the level of Ukrainian teachers’ foreign language competence in reading, a survey was conducted, which has enabled the authors to вуеукьштуt the peculiarities of teachers’ work with foreign texts, the lack of foreign texts that contain topics on various literary genres and reveal a sociocultural component. Eventually, the article offers certain approaches to the adaptation of foreign texts in terms of the learning objectives and students’ communicative needs. The srrategies and criteria, developed and proposed in this study, are a significant extension of the already existing tools that take into account new challenges in modern methods of foreign languages teaching. The prospective areas of further research are the study of the reading materials search engines and their effect on teachers’ foreign language competence in reading.
Keywords: Key words: strategies for selecting foreign language reading materials, criteria for selecting foreign language reading materials, adaptation of foreign language reading materials, foreign language competence in reading.